2022
DOI: 10.9787/kjbs.2022.54.1.51
|View full text |Cite
|
Sign up to set email alerts
|

A White Sesame Variety ‘Nuri’ with Phytophthora Blight Disease Resistance

Abstract: A white sesame variety 'Nuri (Sesamum indicum L.)' with resistance to Phytophthora blight disease was developed in 2016. It was derived from a cross between 'Suwon 131' and 'Yangbaek' in 1999. 'Nuri' has few branches and triple capsules per node. Notably, 'Nuri' exhibited resistance to Phytophthora blight and Fusarium wilt and a yield of approximately 1.19 tons per hectare, 17% higher than that of 'Kopoom'. 'Nuri' presented a crude fat content of 49.0% and protein content of 26.1%. Thus, this variety would con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
3
2
0
Order By: Relevance
“…Higher means were also obtained in NS treatment for these two traits in our study which is in line of findings of Kim et al. (2006). This is also consistent with the results of studies where lower oil content under drought conditions were reported in soybean (Dornbos & Mullen, 1992), canola (Ghobadi et al., 2006), and sunflower (Pekcan et al., 2022).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Higher means were also obtained in NS treatment for these two traits in our study which is in line of findings of Kim et al. (2006). This is also consistent with the results of studies where lower oil content under drought conditions were reported in soybean (Dornbos & Mullen, 1992), canola (Ghobadi et al., 2006), and sunflower (Pekcan et al., 2022).…”
Section: Discussionsupporting
confidence: 93%
“…This result was similar to the findings of Kim et al. (2006) in sesame. Although there was no significant difference between treatments for oleic acid content, however, higher overall mean was recorded for oleic acid content under WS treatment.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations